Crisis-Responsive Hybrid Pedagogy: Lessons from Pandemic-Era Innovations in Inclusive Education - Rami Hariri; Yara Abed; Ziad Khalil (Yayasan Adra Karima Hubbi, 2025)
Background. The COVID-19 pandemic significantly disrupted global education systems, prompting rapid shifts toward hybrid learning models and revealing critical gaps in inclusivity, accessibility, and pedagogical resilience. In response, educators and institutions innovated teaching practices to address diverse learner needs in times of crisis. Purpose. This study investigates how hybrid pedagogical strategies developed during the pandemic contributed to inclusive education and what lessons can be applied for future crisis-resilient instructional design. Method. The research employs a qualitative multiple-case study design involving educators from five inclusive schools across three countries, using semi-structured interviews, document analysis, and virtual classroom observations. Results. Findings indicate that flexible content delivery, adaptive assessment methods, and socio-emotional learning integration were key elements of successful hybrid pedagogies. Teachers reported increased use of assistive technologies, differentiated instruction, and community-based support systems to engage marginalized students. Conclusion. The study concludes that crisis-responsive pedagogy is not merely reactive but can be systematized as a framework for sustainable, inclusive practice. The results highlight the need to embed adaptive capacity, digital equity, and emotional scaffolding into future hybrid education models.